THE FAMILY HEALTH STRATEGY AS AN INSTRUMENT FOR PROMOTING EQUITY IN CONTEXTS OF SOCIAL VULNERABILITY (REMUNOM, 2026)
The Family Health Strategy (FHS) is the main organizational model of Primary Health Care (PHC) in Brazil and plays a central role in consolidating the Unified Health System (SUS). This study aimed to analyze the FHS as an instrument for promoting equity in contexts of social vulnerability. It is a literature review with a qualitative and descriptive-analytical approach, conducted in the SciELO, BVS, LILACS, and CAPES databases, including national publications from 2008 to 2025. Articles addressing the relationship between the FHS, health inequalities, and social vulnerability were included. The findings show that the expansion of FHS coverage occurred in a territorialized manner, with greater concentration among low-income populations, individuals with lower educational levels, and those without private health insurance, indicating a redistributive character. Studies demonstrate an association between higher coverage and reductions in hospitalizations for primary care-sensitive conditions, decreased infant mortality, and improvements in prenatal care quality, with more pronounced effects in socially vulnerable municipalities. These results indicate that the FHS contributes not only to expanding access but also to reducing inequalities in health outcomes. However, the sustainability of equity depends on the consolidation of PHC attributes such as longitudinality, care coordination, and territorial bonding, as well as adequate funding and regulatory stability. It is concluded that the FHS represents a strategic instrument for promoting social justice in health, although its effectiveness relies on institutional strengthening and continuous commitment to the principles of the SUS.